Contemporary robotics with classical kinematic modeling - Bani Hashim, Ahmad Yusairi (Penerbit UTeM Press, 2023)
this book introduces basic concepts and methodologies for mobile robot design, development, and evaluation. developed for the course Advanced Robotics and Robotics Laboratory taught by the author at Universiti Teknikal Malaysia Melaka. The book provides the foundation for further study in the field of mobile robots.